2021
DOI: 10.1088/1755-1315/788/1/012091
|View full text |Cite
|
Sign up to set email alerts
|

Organic Diallyl-n-Sulfide (Dn-S) inhibited the glycogenolysis pathway and heart failure of heat-stressed laying hens

Abstract: Heat stress causes a decrease in metabolic and immune function, thus resulting in decreased production. Natural extracts such as the active compound diallyl-n-sulfide (Dn-S) are one strategy to overcome the adverse effects of heat stress. One hundred and fifty female laying hens, with a mean bodyweight of 1191.38±25.54 g, aged 11 weeks, were used in this experiment to study Dn-S’s impact from garlic on the metabolite profile of the glycogenolysis pathway and heart failure in laying hens. The sample of laying h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…It is associated with the risk of reducing liver tissue damage, which is characterized by a decrease in the value of SGPT and SGOT. Furthermore, the addition of chitosan levels was reported to increase the availability of tissue, repair nutrient precursors consisting of amino acids, carbohydrates, and lipids by increasing the ability to repair -absorptive cells of the ileal villi, as reported by previous studies [34].…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…It is associated with the risk of reducing liver tissue damage, which is characterized by a decrease in the value of SGPT and SGOT. Furthermore, the addition of chitosan levels was reported to increase the availability of tissue, repair nutrient precursors consisting of amino acids, carbohydrates, and lipids by increasing the ability to repair -absorptive cells of the ileal villi, as reported by previous studies [34].…”
Section: Resultssupporting
confidence: 63%
“…The results of previous studies were also reported that chitosan does not only acts as a stimulator of nutrient absorption but also helps to control and balance the levels of the enzymes SGOT and SGPT because it acts as an antioxidant that increases the process of protein anabolism [33][34][35]. The ability of chitosan as an antioxidant implies that it does not only prevent free radicals as a result of the aflatoxin content of the ration but also acts as an anti-inflammatory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This Dn-S capability can be viewed from two aspects. Firstly, Dn-S is able to prevent the activity of enzymes associated with glycogen breakdown (hhh, 8484), possibly through a mechanism of blocking the active site of the enzyme (Adriani et al, 2015(Adriani et al, , 2018(Adriani et al, , 2020Burdick et al, 2011), also by preventing signaling to enzymes (Cai et al, 2017;Dinana et al, 2019), as well as preventing the receptor for extracellular signaling (Gehrke et al, 2013;Ippolito et al, 2014;István et al, 2020, Mushawwir et al 2021a). Secondly, Dn-S appears to be able to completely prevent thermoreceptor and osmoreceptor activation.…”
Section: Resultsmentioning
confidence: 99%
“…The separation of diallyl compounds was carried out according to Block (1985) and Amin et al (2014). The expected characteristics of diallyl isolates are physically clear with a slight yellow, specific odor of garlic, boiling point of 180°C and molecular weight ranging from 141.21 to 146.28 g.mol-1 (Mushawwir et al, 2020c(Mushawwir et al, , 2021a.…”
Section: Preparation Of Diallyl N-sulfide Of Garlicmentioning
confidence: 99%